ANALISIS LAPORAN REALISASI ANGGARAN UNTUK PENGUKURAN KINERJA PEMERINTAH DAERAH KABUPATEN SOLOK SELATAN - Halkadri Fitra; Zahro ilmi Efendi (LPPM Universitas Muhammadiyah Sumatera Barat, 2020)
This study aims to determine the financial performance of the South Solok district government from 2014 to 2018 using data that has been audited by the Indonesian Supreme Audit Board. The data analysis technique is done by using quantitative descriptive method by performing calculations on financial statement data using 10 indicators. The results showed that the ratio of regional financial independence was 8.04% with the category of independence very less, the ratio of regional financial dependency was 91.18% in the very high dependency category, the degree of decentralization of regional finance was 7.32% with the category of the degree of decentralization very less, variance total revenue of Rp -11,434,995,893 in the unprofitable category, growth of total revenue realization of 5.45% in the good category, the effectiveness ratio of total income of 98.57% is in the effective category, the effectiveness ratio of PAD is 102.13% is in the category very effective, the ratio of realization of operating expenditure to realization of total expenditure was 69.04%, the ratio of realization of capital expenditure to realization of total expenditure was 30.77%, and the ratio of efficiency of total expenditure in 2014 to 2018 was 92.75% in the less category efficient.